Investigation of effect of machine layout on productivity and utilization level: what if simulation approach - Bourini, Islam Faisal; Al Hazza, Muataz Hazza Faizi; Taha, Assem Hatem (Dhaka University of Engineering & Technology, 2018)
Designing and selecting the material handling system is a vital factor for any production line, and as result for the whole manufacturing system. Poor design and unsuitable handling equipment may increase the risk of having bottlenecks, longer production time and as a result the higher total production cost. One of the useful and effective tools are using “what if” simulation techniques. However, this technique needs effective simulation software. The main objective for this research is to simulate different types of handling system using what if scenario. To achieve the objective of the research, Delmia Quest software has been used to simulate two different systems: manual system and conveyers system for the same production line and analyses the differences in terms of utilization and production rate. The results obtained have been analysed and appraised to induce the bottleneck locations, productivity and utilizations of the machines and material handling systems used in the design system. Finally, the best model have been developed to increase the productivity, utilizations of the machines, material handling systems and to minimize the bottleneck locations.